Cerebral ventriculitis associated with Achromobacter xylosoxidans. Issue 2 (February 1978) - Shigeta, S; Yasunaga, Y; Honzumi, K; Okamura, H; Kumata, R; Endo, S
Abstract : Six patients in the neurosurgical ward of Fukushima Medical College Hospital suffering from ventriculitis due to Achromobacter xylosoxidans infection had undergone craniotomy or cranial trepanation before the infection. The strains of A. xylosoxidans isolated from the patients were resistant to streptomycin, ampicillin, cephaloridine, gentamicin, and colistin. They were also resistant to chlorhexidine digluconate (Hibitane) in a concentration of 2%. When a study of the chlorhexidine used in the hospital was carried out four strains of A. xylosoxidans were isolated from 20 containers of chlorhexidine solution in the surgical ward but not from those in the operating theatre.